Gas Phase Oligomerization of Isobutene over Acid Treated Kaolinite Clay Catalyst - Dhaifallah Aldhayan; Ahmed Aouissi (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Natural Kaolin Clay was calcined and treated by sulfuric acid. The resulting solid acid catalyst was characterized by FTIR, TGA, and X-ray powder diffraction (XRD) and tested for isobutene oligomerization in a gas phase. The characterization results showed that the acid treated clay underwent chemical and structural transformations. After acid treatment, the Si/Al ratio was increased, and the crystalline raw clay became amorphous. The effects of various parameters such as reaction temperature, reaction time and contact time on isobutene oligomerization were investigated. Catalytic tests showed that isobutene oligomerization led to dimers and trimers as major products. Tetramers were obtained as by- products. At relatively high reaction temperatures and long contact times, the conversion was enhanced while the selectivity of dimers was decreased in favor of higher oligomers.